Monitoring conduction disturbances following TAVR: Feasibility study of early discharge using a novel telemetry patch. (1st October 2022) - Scotti, Andrea; Sturla, Matteo; Coisne, Augustin; Assafin, Manaf; Chau, Mei; Ho, Edwin C.; Granada, Juan F.; Ferrick, Kevin J.; Di Biase, Luigi; Latib, Azeem
Abstract: Introduction: Despite the technological advances and increasing operator experience, the rate of permanent pacemaker implantation (PPI) after transcatheter aortic valve replacement (TAVR) has not decreased over time. With a continuous downward trend in post-TAVR length of stay, prolonged home-monitoring may have a key role in detecting potentially serious conduction abnormalities after TAVR discharge. Methods: In this study, the ZioPatch-AT monitor was used to detect conduction abnormalities after TAVR discharge. The cardiac monitoring device was systematically provided to all patients having pre-existing right bundle branch block or developing intra−/peri-procedural conduction disturbances, in the absence of guideline indication for PPI at discharge. Results: From a total of 75 patients at high-risk of conduction disturbances, 8 (11%) of them underwent PPI and most of them (6/8) were detected before symptoms' occurrence. Paired analysis between baseline and discharge electrocardiograms detected a significant widening of the QRS in all patients; on the contrary, PR length was significantly increased only in the group experiencing HAVB after discharge ( p  < 0.01). Conclusions: In an early post-TAVR discharge era, 30-day outpatient cardiac rhythm monitoring is potentially a safe solution to allow timely recognition of new conduction disturbances requiring PPI. Highlights: Despite the technological advances and increasing operator experience, the rate of permanent pacemaker implantation (PPI) after transcatheter aortic valve replacement (TAVR) has not decreased over time. With a continuous downward trend in post-TAVR length of stay, prolonged home-monitoring may have a key role in detecting potentially serious conduction abnormalities after TAVR discharge. A percentage of 11% patients at high-risk of conduction disturbances required PPI, and most of them (6/8) were detected before symptoms' occurrence. In an early post-TAVR discharge era, 30-day outpatient cardiac rhythm monitoring is potentially a safe solution to allow timely recognition of new conduction disturbances requiring PPI.